LESYA UKRAINKA AND VASYL STEPHANYK: SEMANTICS OF «STONE» IN THE WORLD OF LITERATURE - Vasylyk , L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
From the point of view of comparative studies the idea of artistic meaning of the symbol of «stone» is research ed in the works of Ukrainian writers Vasyl Stefanyk and Lesya Ukrainka.